Energy scenarios to move toward a zero-emission economic of Vietnam - Nguyễn Minh Dũng; Võ Viết Cường (Journal of Technical Education Science, 2012)
Energy, particularly electric energy has been proven to be a driving force in economic development for every country, including Vietnam. The objective of this study is to build various scenarios of energy – environment, which may occur in Vietnam from 2011 to 2030. Factors that influence the energy demands and level of environmental emissions include population growth rate, GDP growth rate, planned development of field economics, level of urbanization, production technology and energy consumption, etc., are investigated in this study. Software, LEAP (Long-range Energy Alternative Planning System) is used to analyze and simulate scenarios of energy – environment. The results show that primary energy demand in Vietnam tends to increase, with a value of 212.21MTOE (Million Tons of Oil Equivalent) in Reference scenario, 224.63MTOE in Average growth scenario and 232.53MTOE in High growth scenario in year 2030. While, the total demand of energy consumption in economic fields is predicted to come to an amount of 148.2MTOE, 152.1MTOE and 152.7MTOE along with scenarios in 2030. And, CO2 emission of Reference, Average growth and High growth scenarios are 571, 552 and 541 million tones of CO2 equivalent, respectively.